Shelleys Romantic Passion in Ode to the West Wind: Its Impact on Farrukh Ahmad - Hosain, Md Iqbal (IIUC Studies, 2016)
The paper intends to explore a parallel between Shelley and Farrukh Ahmad through a minute analysis of some of their celebrated poems pregnant with romantic passion. Ode to the West Wind, which has been considered as one of the most significant poems of Shelley, conceives his utmost romantic idea that corresponds to the romantic spirit of Farrukh Ahmad expressed in Jhod and Boishakh, two of his famous poems. In Ode to the West Wind Shelley urges the west wind to destroy the aged old society full of corruption and injustice and at the same time pleads it to preserve the society by spreading the seeds of new hope and regeneration. So does Farrukh Ahmad in his Jhod and Boishakh. Though their beliefs and ideologies are not alike, they have taken the west wind as an emblem of destroyer and preserver. IIUC Studies Vol.12 December 2015: 63-70